Agronomic Performance of Different Open-Pollinated Beetroot Genotypes Grown Under Organic Farming Conditions - Khadijeh Yasaminshirazi; Jens Hartung; René Groenen; Thomas Heinze; Michael Fleck; Sabine Zikeli; Simone Graeff-Hoenninger (Agronomy, 2020)
Due to the increase of the organic cultivation of beetroot and its growing importance as a functional food, the potential advantages of open-pollinated genotypes as an alternative for F1 hybrid genotypes has been investigated. In this regard, six field experiments were carried out in 2017 and 2018 in three different locations to investigate the agronomic potential of new and existing open-pollinated genotypes of beetroot and their performance under the specific conditions of organic agriculture. Fifteen beetroot genotypes, including one F1 hybrid as a commercial control and one breeding line, were compared regarding their total and marketable yield, individual beet weight, diameter of beet, and leaves-growth-base width. Furthermore, five randomly selected beetroots meeting common marketable criteria were evaluated optically with regard to skin smoothness, corky surface, root tail, scab incidence, and uniformity. Results of this study indicated a significant impact of genotype on eight of the assessed traits. The cylindrical-shaped genotype, Carillon RZ, demonstrated significantly higher total and marketable yields, with 53.28 ± 3.34 t ha−1 and 44.96 ± 3.50 t ha−1, respectively, compared to the yellow-colored genotype, Burpees Golden, which obtained the lowest total yield, 36.06 ± 3.38 t ha−1, and marketable yield, 27.92 ± 3.55 t ha−1. Moreover, the comparison of the open-pollinated genotypes with the F1 hybrid, Monty RZ F1, revealed that except for the traits yield, scab, and uniformity, the open-pollinated genotypes indicated desirable competitive outcomes and thus offer suitable alternatives for organic cropping systems. Overall, the observed genetic variability can be beneficial for breeding and food product development.